2021
DOI: 10.3389/fpsyt.2021.676914
|View full text |Cite
|
Sign up to set email alerts
|

Public Psychosocial and Behavioral Responses in the First Wave of COVID-19 Pandemic: A Large Survey in China

Abstract: Background: The COVID-19 has grown into a global pandemic. This study investigated the public psychosocial and behavioral responses through different time periods of the pandemic, and assessed whether these changes are different in age, gender, and region.Methods: A three-phase survey was conducted through the DaDui Social Q&A Software for COVID-19. A total of 13,214 effective responses of COVID-19 were collected. Statistical analysis was performed based on their basic information and psychosocial resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It was not only a public health problem but also, on a large scale, an information crisis. In China, data from a 3-phase survey, collected during the first wave of COVID-19, showed low cooperation with prevention and control measures in the early stages, followed by a gradual increase as the pandemic progressed [ 22 ]. We aimed to understand the population's perception of the need for self-care and social distancing, considering the observed individual behavior and its consequences.…”
Section: Discussionmentioning
confidence: 99%
“…It was not only a public health problem but also, on a large scale, an information crisis. In China, data from a 3-phase survey, collected during the first wave of COVID-19, showed low cooperation with prevention and control measures in the early stages, followed by a gradual increase as the pandemic progressed [ 22 ]. We aimed to understand the population's perception of the need for self-care and social distancing, considering the observed individual behavior and its consequences.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) reported that noncommunicable diseases (eg, heart disease, stroke, cancer, diabetes, and chronic lung disease) were the cause of 71% of deaths worldwide in 2017 [ 1 ]. In addition, the exceptional regulatory measures taken to fight the COVID-19 pandemic have had a negative impact on the psychological health of citizens as made evident by a surge in incidences of psychological crises [ 2 ]. The extraordinary context generated by the COVID-19 pandemic has posed unprecedented challenges for governments [ 3 , 4 ] and has led to a redefinition of human activities within our societies, namely an acceleration in the digital transformation of health care [ 5 ].…”
Section: Introductionmentioning
confidence: 99%